SINUSOIDAL PWM-BASED CONTROL AND DEVELOPMENT OF A 7-LEVEL CHB MULTILEVEL INVERTER - Khaidzir, Muhammad Luqman Nurhakim; KHALID, KHAIRUL NADIAH; Zainuddin, Isa; Abdul Wahab, Nurul Husna; Ali Mohd Jobran, Junaidah (Journal of Engineering and Technology (JET), 2026)
The development of a 7-level Cascaded H-Bridge (CHB) multilevel inverter involves designing an advanced power electronics system capable of delivering high-quality, efficient AC power. This inverter topology comprises multiple H-bridge cells connected in series, each generating discrete voltage levels. By combining these levels, the inverter produces a stepped output waveform with improved quality, reduced harmonic distortion, and lower stress on switching components. The "7-level" designation indicates the inverter can generate seven distinct voltage levels, enhance control precision and resulting in a smoother AC waveform. Multilevel inverters are especially beneficial in applications that demand clean and stable power, such as sensitive electronic loads. Although LED lighting applications are not the primary focus of this study, the characteristics of multilevel inverters align well with the requirements of such systems, which typically demand low harmonic content and stable operation for optimal performance. Achieving this performance requires a solid understanding of power electronic design, modulation strategies such as Sinusoidal Pulse Width Modulation (SPWM), and system integration. The design process entails careful component selection, effective control implementation, and rigorous testing to ensure compliance with performance standards and operational reliability. This technical study focuses on the simulation, development, and evaluation of a 7-level CHB inverter using SPWM to assess its performance for general power conversion purposes.